Error Analysis and Interlanguage in the Use of the Term ‘ICT’ in an Online Learner Corpus - Torrado-Cespón, Milagros; Díaz Lage, José María (Complutense Journal of English Studies, 2018)
The main objective of this study is to highlight the need to advise students to revise their online written productions to avoid the incorrect use of forms which differ from their L1. In order to do so, this paper explores a specific error: misuse of the initialism 'ICT'. Even though the analysis deals with this term, the conclusion can be applied to similar cases. The subjects are university students who use English as a vehicular language in the classroom but who have very different levels of proficiency. After analysing their written productions in an online forum it was observed that misuse of 'ICT' could be either an error, due to a gap in knowledge, or a mistake, due to interlingual transfer. Taking Selinker's (1972) and Corder's (1981) theories as a starting point, we then explore what to do in these cases considering the specific form of instruction that these students receive. Consequently, explicit teaching of the term in the classroom is proposed taking into account the learners' age factor and the revised theories.
Keywords: error analysis; interlanguage; english as a vehicular language; explicit vs. implicit teaching; Emerging